Ejection Patterns in the DG Tau Jet over the Last 40 yr: Insights into Mass Accretion Variability - Tae-Soo Pyo; Masahiko Hayashi; Michihiro Takami; Tracy L. Beck (The Astrophysical Journal, 2024)
We aim to clarify the link between mass accretion and ejection by analyzing DG Tau’s jet observations from optical and near-infrared data spanning 1984–2019, alongside photometric variations between 1983 and 2015. We classified 12 moving knot groups among 17 total knot groups based on their constant proper motions and comparable radial velocities. A strong correlation emerges between the deprojected flow velocities of the knots and the photometric magnitudes of DG Tau. From 1983 to 1995, as the deprojected ejection velocities surged from ∼273 ± 15 to ∼427 ± 16 km s ^−1 , the photometric magnitudes ( V ) concurrently brightened from 12.3 to 11.4. Notably, when DG Tau became brighter than 12.2 in the V band, its ( B − V ) color shifted bluer than its intrinsic color range of K5–M0. During this period, the launching point of the jet in the protoplanetary disk moved closer to 0.06 au from the star in 1995. Following a V magnitude drop from 11.7 to 13.4 in 1998, the star may have experienced significant extinction due to a dust wall created by the disk wind during the ejection of the high-velocity knot in 1999. Since then, the magnitude became fainter than 12.2, the ( B − V ) and ( V − R ) colors became redder, and the deprojected velocities consistently remained below 200 km s ^−1 . The launching point of the jet then moved away to ∼0.45 au by 2008. The prevailing factor influencing photometric magnitude appears to be the active mass accretion causing the variable mass ejection velocities.